Fatal Rhinofacial Mycosis Due to Aspergillus nomiae: Case Report and Review of Published Literature - Zhou, Ya Bin; Li, Dong Ming; Houbraken, Jos; Sun, Ting Ting; de Hoog, G. Sybren (Frontiers in Microbiology, 2020)
Background A 73-year-old female suffering from acute myeloid leukemia presented with progressive rhinofacial mycosis. Suspecting it to be mucormycosis, the antifungal amphotericin B (AMB) was administered empirically, but the patient did not respond as planned. The fungus was then isolated from the biopsied tissue and morphologically identified as a species of Aspergillus. Necrosis progressed and she died of cerebral hemorrhage. Since Aspergillus flavus is susceptible to AMB, and several other Aspergillus species can be misidentified as A. flavus, the observed resistance necessitated a re-examination of the fungal isolate. Methods The fungal strain was re-isolated and re-examined morphologically. Additionally, genomic DNA was extracted from the fungus and sequences were obtained from three genomic regions [the rDNA internal transcribed spacer (ITS) region, and portions of the β-tubulin and calmodulin genes] to more accurately identify this Aspergillus strain. Its antifungal susceptibility was assessed using multiple compounds and our findings were compared with literature data. Results The fungal culture again yielded an Aspergillus isolate morphologically identical to A. flavus. Molecular analyses, however, revealed the strain to be A. nomiae, a close relative of A. flavus in section Flavi, and it exhibited resistance to AMB. Reviewing the literature, only five other cases of A. nomiae infection in humans have been reported worldwide. Conclusion and Clinical Importance The rhinofacial mycosis of the patient was actually due to A. nomiae. The initial misidentification of the fungus, coupled with its resistance to AMB, could be the reason treatment did not help the patient. We postulate that clinical A. nomiae infections may be underreported and that accurate and speedy pathogen identification is important so that an effective antifungal regimen can be administered.